2017
DOI: 10.4238/gmr16039278
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance and expression of PUMA, MCL-1, and p53 in human renal cell carcinoma and para-carcinoma tissues

Abstract: ABSTRACT. We investigated the expression level of p53 upregulated modulator of apoptosis (PUMA), myeloid cell leukemia-I (MCL-1), and p53 in renal cell carcinoma (RCC) and para-carcinoma tissues, as well as their clinical significance. The expression levels of PUMA, MCL-1, and p53 in RCC and para-carcinoma tissues were measured using immunohistochemical and quantitative real-time PCR methods. Correlations between protein expression and pathological characteristics were analyzed. Renal clear cell carcinoma show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Puma is an important pro-apoptotic gene and serves an important role in the initiation of cell apoptosis and the induction of numerous other diseases, such as hepatocyte injury and bone marrow hyperplasia (40). Puma is reported to be involved in p53-dependent or independent cell apoptosis and tumor processing (40)(41)(42). Puma is significantly upregulated when apoptosis occurs (43).…”
Section: Discussionmentioning
confidence: 99%
“…Puma is an important pro-apoptotic gene and serves an important role in the initiation of cell apoptosis and the induction of numerous other diseases, such as hepatocyte injury and bone marrow hyperplasia (40). Puma is reported to be involved in p53-dependent or independent cell apoptosis and tumor processing (40)(41)(42). Puma is significantly upregulated when apoptosis occurs (43).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the association of MCL-1 with tumors is a natural consequence of its mechanism. Numerous studies have reported that high MCL-1 expression is linked to the occurrence, progression, metastasis, and poor prognosis of various tumors, including human breast, renal, hepatocellular, gastric, pulmonary, ovarian cancers, and lymphoma [ 2 , 6 12 ]. Specifically, in human breast cancer, a study using MMTV-PyMT mice revealed high MCL-1 expression in both primary mammary tumors and metastatic lesions.…”
Section: Introductionmentioning
confidence: 99%